Evaluation of the Antimicrobial Effect of Ethanolic Extracts of Sage and Rue as a Root Canal Irrigants (An In Vivo Study). - Maha M Al -Bazzaz (University of Mosul, College of Dentistry, 2011)
Aims: To evaluate the antimicrobial effect of the ethanolic extracts of Ruta graveolens (Rue) and Sal-via officinalis (Sage) in a concentration of 0.2% and compare the results with the same concentration of chlorhexidine 0.2% (CHX) and normal saline on root canal bacteria using the above plant extracts as an irrigating solutions clinically. Materials and Methods: Thirty five uniradicular teeth with necrotic pulps were chosen. The patients were divided randomly into four groups, 10 patients for groups I, II and III and 5 patients for group IV. Using 0.2% ethanolic extract of Sage, 0.2% ethanolic extract of Rue, 0.2% chlorhexidine gluconate (CHX) and normal saline, respectively. Samples were obtained from the canal at the beginning of the first and second appointments, at the end of the second appointment and at the beginning of the third appointment using wet sterile paper points. Results: The results revealed that 0.2% of the ethanolic extract of both Sage and Rue have a significant antimicrobial effect when used clinically as an endodontic irrigant, and was significantly not different from 0.2% chlorhex-idine gluconate (CHX) and significantly different from normal saline. Conclusions: Rue and Sage demonstrated antimicrobial effects on the root canal bacteria (both aerobic and anaerobic) used as en-dodontic irrigants compared with CHX.